2015
DOI: 10.1016/j.rmb.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental observations on the morphology of Procamallanus (Spirocamallanus) hilarii (Nematoda: Camallanidae) parasitizing two species of Astyanax (Characiformes: Characidae) and ecological analyses

Abstract: Revista Mexicana de Biodiversidad 86 (2015) 590-596 Taxonomy and systematics Supplemental observations on the morphology of Procamallanus (Spirocamallanus) hilarii (Nematoda: Camallanidae) parasitizing two species of Astyanax (Characiformes: Characidae) and ecological analyses Observaciones suplementarias sobre la morfología de Procamallanus (Spirocamallanus) hilarii (Nematoda: Camallanidae) parasitando dos especies de Astyanax (Characiformes: Characidae) y análisis ecológico Abstract Procamallanus (Spirocamal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…fasciatus (Cuvier, 1819) were collected with seine nets between March 2012 and December 2013 from Lake Guaíba, municipalities of Guaíba (30°08.28'S, 51°18.53'W) and Barra do Ribeiro (30°17.11'S, 51°18.01'W), State of Rio Grande do Sul, Brazil. Procedures of transportation and host identification were made according Gallas et al (2015). Nematodes were collected, fixed, and preserved following Amato and Amato (2010), and they were temporarily mounted and cleared in Amann's lactophenol (Humason 1979).…”
Section: Methodsmentioning
confidence: 99%
“…fasciatus (Cuvier, 1819) were collected with seine nets between March 2012 and December 2013 from Lake Guaíba, municipalities of Guaíba (30°08.28'S, 51°18.53'W) and Barra do Ribeiro (30°17.11'S, 51°18.01'W), State of Rio Grande do Sul, Brazil. Procedures of transportation and host identification were made according Gallas et al (2015). Nematodes were collected, fixed, and preserved following Amato and Amato (2010), and they were temporarily mounted and cleared in Amann's lactophenol (Humason 1979).…”
Section: Methodsmentioning
confidence: 99%
“…fasciatus (Cuvier, 1819), Astyanax henseli Melo &Buckup, 2006 andAstyanax lacustris (Lütken, 1875). Until now, two species of digenetic trematodes, two species of monogeneans and one species of nematode were recorded from species of Astyanax in the Lake Guaíba (Fortes & Hoffmann 1999, Gallas et al 2014, 2015, 2016), but no acanthocephalans were observed parasitizing species of this genus.…”
Section: Introductionmentioning
confidence: 99%